2022
DOI: 10.3390/jcm11226774
|View full text |Cite
|
Sign up to set email alerts
|

Airway Bacterial Biodiversity in Exhaled Breath Condensates of Asthmatic Children—Does It Differ from the Healthy Ones?

Abstract: Asthma etiopathology is still not fully determined. One of its possible causes can be found in airway microbiome dysbiosis. The study’s purpose was to determine whether there are any significant differences in the bacterial microbiome diversity of lower airways microbiota of asthmatic children, since knowledge of this topic is very scarce. To the authors’ knowledge, this is the first research using exhaled breath condensates in children’s lower airways for bacterial assessment. Exhaled breath condensates (EBC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…Studies have shown that Proteobacteria are abundant in the respiratory tract of asthmatic patients 43 . In the airway microbiota of asthmatic patients, the most dominant bacteria at the phylum level are Firmicutes, followed by Proteobacteria and Actinobacteriota 44 . In this study, we found that microbial alpha diversity reduced, the abundance of Actinobacteriota and Proteobacteria increased and the abundance of Firmicutes decreased in the gut of asthmatic mice.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Studies have shown that Proteobacteria are abundant in the respiratory tract of asthmatic patients 43 . In the airway microbiota of asthmatic patients, the most dominant bacteria at the phylum level are Firmicutes, followed by Proteobacteria and Actinobacteriota 44 . In this study, we found that microbial alpha diversity reduced, the abundance of Actinobacteriota and Proteobacteria increased and the abundance of Firmicutes decreased in the gut of asthmatic mice.…”
Section: Discussionsupporting
confidence: 52%
“…43 In the airway microbiota of asthmatic patients, the most dominant bacteria at the phylum level are Firmicutes, followed by Proteobacteria and Actinobacteriota. 44 In this study, we found that microbial alpha diversity reduced, the abundance of Actinobacteriota…”
Section: Discussionmentioning
confidence: 54%
“…The nasal brushes also had greater bacterial richness than that of the washes [ 17 ]. The exhaled breath condensates had lower alpha diversity than that of the oropharyngeal samples [ 44 ]. Because of the sampling procedure, the EBC and induced-sputum samples could be contaminated with upper respiratory bacteria, of which researchers should be aware while assessing the outcomes of studies with those sampling methods.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presented studies do not provide sufficient information about the influence of asthma treatment on bacterial microbiome. In one study, the asthma medication intake in the lower-airway samples of the asthmatics was statistically relevant in terms of beta diversity ( n = 14 vs. 5, p = 0.014) [ 44 ]. This topic needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation